Soil Quality Engineering Using Vermicompost and its Effect on the Corn (Zea mays L.) Production in Coastal Area - Riwandi Riwandi; Hasanudin Hasanudin; Herry Gusmara; Anandyawati Anandyawati (JOURNAL OF TROPICAL SOILS, 2020)
The low quality of Entisol is caused by low availability of nitrogen, phosphorus, and potassium as well as low soil pH, so the addition of vermicompost is necessary. The purpose of this study was to determine the effect of vermicompost application on soil quality and to obtain the highest vermicompost dosage on the availability of nutrients such as N, P, K, and the yield of corn. The field experiment used a Randomized Completely Block Design (RCBD) with 7 dosages of vermicompost and three replications. The treatments were V0 = 0; V1 = 5; V2 = 10; V3 = 15; V4 = 20; V5 = 25; V6 = 30 Mg ha-1. Variables observed consisted of 1) initial soil and vermicompost characterization analysis, 2) soil analysis and N, P, and K content in leaves, and yield of corn. The results showed that Entisol was classified as low quality; however, vermicompost quality complied with the requirements of quality organic fertilizer. The experiment also indicated that the highest pH of Entisol (5.31) and K content in corn leaves (2.12%) were obtained at a dose of vermicompost 25 Mg ha-1. Meanwhile, the highest weight of husked corn cobs (415.55 g plant-1) and weight of unhusked corn cob (351.11 g plant-1) were obtained at a vermicompost dose of 15 Mg ha-1.